Expression of Interleukin-17A in Lung Tissues of Irradiated Mice and the Influence of Dexamethasone - Li-Ping Wang; Yan-Wen Wang; Bao-Zhong Wang; Gui-Ming Sun; Xiu-Yu Wang; Jun-long Xu (The Scientific World Journal)
Purpose. To investigate the expressions of IL-17A in different phases of radiation-induced lung injury and the effect of dexamethasone. Methods. The thorax of C57BL/6 mice was irradiated with 15 Gy rays. Mice from dexamethasone-treated group were injected intraperitoneally with dexamethasone (0.42 mg/kg/day) every day for the first month after irradiation. IL-17A in lung tissues was detected by immunohistochemistry. IL-17A, TGF-β1, and IL-6 in bronchoalveolar lavage fluid were detected by ELISA. Lung inflammation and collagen deposition were observed by H&E and Masson methods. The degree of alveolitis and fibrosis was judged according to scoring. Results. IL-17A expression was appreciable at 1 week, peaked at 4 weeks, and subsequently declined at 8 weeks after irradiation. IL-17A was reduced after dexamethasone application at all the observation periods. Dexamethasone also inhibited expressions of TGF-β, IL-6, and TNF-α in bronchoalveolar lavage fluid. Moreover, dexamethasone attenuated the severity of lung injury by reducing the infiltration of inflammatory cells and collagen deposition. Terms of survival and the time of death in mice of treatment group were postponed and survival rate was improved. Conclusions. IL-17A plays an important role in the process of radiation-induced lung injury. And dexamethasone may provide a protective role in lung injury induced by radiation.